Improving CBT supervision. Four years of implementing NES Specialist Supervision Training for CBT in Scotland. (2020) - O'Neill, Nathan; Albiston, Mairi; Ferguson, Sandra; Nicklas, Leeanne
Abstract: NHS Education for Scotland (NES) plays a lead role in training the NHS Psychological Therapies workforce across Scotland. Ferguson et al . (2016 ) outlined the challenges, opportunities and proposed evaluation of the NES Specialist Supervision Training in Cognitive Behavioural Therapy (NESSST-CBT). The aims of the training were to provide an evidence-based, flexible and learner-focused training in CBT specific supervision competencies. This paper will provide an update on the evaluation of the training using Kirkpatrick's Impact Evaluation Model (1967, 1987 ). Results indicate that: (1) delegates rated the training experience positively in various ways; (2) delegates described increases in their confidence and competence in using structured measures of CBT and supervision; (3) a majority of delegates completing a 3-month follow-up questionnaire described continued use of a structured CBT measure in supervision and for self-reflection; and (4) 392 psychological therapists in Scotland have now been formally trained in CBT specific supervision skills. NESSST-CBT continues to adapt and improve as a resource for staff as NES moves forward in its Digital Strategy for Scotland's NHS and partnership staff. Further implications of this are discussed, as well as limitations of the study. Key learning aims: (1) Readers will be able to further understand the multi-faceted role of NHS Education for Scotland in implementing CBT supervision training in Scotland. (2) Readers will be able to list three key outcomes from the feedback data on 4 years of a specialist supervision blended-learning training for CBT supervision. (3) Readers will be able to identify three key limitations of the study and recommendations for future research.